3 - Towards a New Conceptual Framework of Student Activism in South Africa - Teferra, Damtew; Ntuli, Mthokozisi Emmanuel (Journal of Higher Education in Africa, 2022)
While the phenomenon of student activism is not new in South Africa, it has escalated recently and has taken on new forms. The literature expounds the emergence of a new modality of student activism in the form of protest movements employing social media as mobilisation tools. While such activism traditionally manifested itself in student representation in university governance structures and student demonstrations, protest movements and social media have emerged as its modern manifestation in South Africa. This article systematically analyses extant theories and conceptual frameworks to assess their relevance to these new modalities. After closely analysing key conceptual frameworks including Stakeholder Theory, the Ideal-type Regime of Governance Model and the Activist Leadership Model, it demonstrates their limitations for describing the emerging trends of student activism in South Africa, the paper proposes a new and robust conceptual model called Unbounded Student Activism.